Capybara social structure and dispersal patterns: Variations on a theme - Herrera, Emilio A. (2011)
Capybaras, (Hydrochoerus hydrochaeris) are large, herbivorous New World hystricomorphs, common in the seasonally flooded savannas of tropical and subtropical South America. In this paper we review the social structure and dynamics of capybaras across much of their geographic range. Wherever they have been studied capybaras live in groups. Capybara groups are stable social units composed of adult males and females (sex ratio biased toward females) with their young. A linear dominance hierarchy characterizes interactions among males, and the dominant male obtains most matings. Group sizes range from 6 to 16 adult members and vary with habitat characteristics and population density. At higher densities group sizes and the proportion of floaters (apparently unaffiliated animals; mostly males) increase. In 1 low-density location dispersal appears to occur in groups of both sexes, whereas in another location, where density is higher, males disperse and females are philopatric. We also discuss more conceptual issues (mostly proximate and ultimate mechanisms) that relate to intraspecific variation in social behavior in general, and capybaras in particular.